Time Course of Antispike Antibody Titer after Administration of BNT162b2 mRNA COVID-19 Vaccine in a Patient with Rheumatoid Arthritis on Methotrexate - Shinohara, Satoshi; Hirose, Yasuhiro (Case Reports in Rheumatology, 2023)
Methotrexate, an anchor drug for rheumatoid arthritis, hinders the immunogenicity of mRNA COVID-19 vaccines. Therefore, an optimal vaccine strategy for patients with rheumatoid arthritis receiving methotrexate is vital. We monitored antispike antibody titers after BNT162b2 mRNA COVID-19 vaccination in seven healthcare workers and one methotrexate-treated rheumatoid arthritis patient. The antispike antibody titers of healthcare workers significantly increased immediately after primary vaccination and then continued to decrease, whereas those of the rheumatoid arthritis patient were significantly lower immediately after primary vaccination and then increased. The titers in all participants dramatically increased 1-month postbooster. These changes over time may suggest that in the methotrexate-treated rheumatoid arthritis patient, the generation of short-lived plasma cells was strongly suppressed; in contrast, the generation of long-lived plasma cells and memory B cells was intact. For methotrexate-treated rheumatoid arthritis patients, it is important to complete the primary and booster vaccination series to ensure sufficient immunity against COVID-19.